The role of serum matrix metalloproteinase-9 levels in the etiopathogenesis of nasal polyps - Acar, Mustafa; Erdem Gür, Özer; Kaymakçı, Mustafa; Çiftçi, Onur; Buğdaycı, Güler; Özdem, Cafer (ENT Updates, 2012)
Objective: The aim of this study is to reveal the role of matrix metalloproteinase-9 in the pathogenesis of nasal polyps by comparing its levels in normal healthy subjects, and patients with nasal polyps. Our second aim is to demonstrate the correlation (if any) between white blood cell counts, age, gender of the patients presence of asthma, and MMP-9 levels. Methods: Serum samples of patients were obtained and kept at -70°C. Quantikine kit (R&D System Inc, Minneapolis, MN, USA) micro-ELISA (Enzyme-Linked Immunosorbent Assay) method was used to estimate plasma matrix metalloproteinase-9 levels. Serum matrix metalloproteinase-9 values of the control, and the patient groups were compared. The correlation between age, gender of the study subjects, white blood cell counts and the presence of asthma was investigated. Results: Serum matrix metalloproteinase-9 values were significantly higher in patients with nasal polyps relative to the control group. White blood cell counts in the group with nasal polyps were higher without any statistically significant difference between the groups. Any correlation between matrix metalloproteinase-9 values, age, and gender was not found. In addition, any correlation was not detected between concomitant asthmatic disease and matrix metalloproteinase-9 values. Conclusion: Significantly, higher matrix metalloproteinase-9 values in patients with nasal polyps support our opinion suggesting the role of this protein in the etiopathogenesis of this disease.